The Mediating Effect of Brand Trust on Purchase Decisions through Perceived Quality and Health Consciousness Using PLS-SEM - Saripa Zihad Mulahela; Muhammad Mujahid Dakwah (Jayapangus Press, 2026)
The growing adoption of healthy lifestyles has increasingly challenged the consumption of carbonated beverages, which are widely perceived as unhealthy products. Nevertheless, some brands remain competitive due to strong perceived quality and consumer trust. This study aims to examine the mediating role of brand trust in the relationships among perceived quality, health consciousness, and purchase decisions for Big Cola, addressing inconsistent findings on the Influence of health consciousness on unhealthy product consumption. This study employed a quantitative explanatory design using Partial Least Squares Structural Equation Modeling (PLS-SEM). Data were collected from 200 respondents who had previously consumed Big Cola through purposive sampling. Measurement items were assessed using a five-point Likert scale, and the analysis was conducted using SmartPLS 4.0 to evaluate both the measurement and structural models. The results indicate that perceived quality has a strong positive effect on brand trust and a positive Influence on purchase decisions. In contrast, health consciousness negatively affects purchase decisions, suggesting that greater health awareness reduces consumers' willingness to buy carbonated beverages. Furthermore, brand trust plays an important mediating role by strengthening the effect of perceived quality on purchase decisions and partially mitigating the negative Influence of health consciousness. The structural model demonstrates strong explanatory power, with R² values of 0.72 for brand trust and 0.81 for purchase decisions. This study provides empirical evidence that health consciousness shows a negative but weak effect, indicating a limited deterrent role in unhealthy product consumption, while brand trust remains a key mechanism sustaining purchase behavior.